2012
DOI: 10.1155/2012/907971
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Growth Pattern, Proteolysis and Angiogenesis in Chemonaive Patients Resected for Multiple Colorectal Liver Metastases

Abstract: The purpose of this study was to characterise growth patterns, proteolysis, and angiogenesis in colorectal liver metastases from chemonaive patients with multiple liver metastases. Twenty-four patients were included in the study, resected for a median of 2.6 metastases. The growth pattern distribution was 25.8% desmoplastic, 33.9% pushing, and 21% replacement. In 20 patients, identical growth patterns were detected in all metastases, but in 8 of these patients, a second growth pattern was also present in one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 35 publications
7
68
1
Order By: Relevance
“…[1][2][3][4] The desmoplastic growth pattern is consistent with high proteolytic activity. 4,5 Although the morphological categorization described by Vermeulen et al 3 has been recognized in various studies, the prognostic significance remains controversial. Van den Eynden et al 3 identified pushing growth as an independent predictor of poor 2-year survival, whereas Nagashima et al 6 found a detrimental effect of an infiltrative tumor margin similar to the replacement pattern.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…[1][2][3][4] The desmoplastic growth pattern is consistent with high proteolytic activity. 4,5 Although the morphological categorization described by Vermeulen et al 3 has been recognized in various studies, the prognostic significance remains controversial. Van den Eynden et al 3 identified pushing growth as an independent predictor of poor 2-year survival, whereas Nagashima et al 6 found a detrimental effect of an infiltrative tumor margin similar to the replacement pattern.…”
mentioning
confidence: 63%
“…Metastases with mixed-type margins have been reported earlier, but guidelines for cut-off point and categorization have not yet been published. [1][2][3][4] In previous studies, little intra-and inter-observer variability was found for Vermeulen's procedure. 1,2,4 After consensus readings by two observers (KN and BV) of 20 cases, one observer (KN) assessed all sections.…”
Section: Histological Assessmentmentioning
confidence: 90%
“…Different histologic patterns in the tumor-liver interface of solid tumors were described by Terayama and colleagues (94) and Vermeulen and colleagues (95), based on microscopic examination of hematoxylin and eosin and Gordon Sweet's silver (reticulin) staining. This assessment is reproducible (95,96). Figure 2 summarizes the characteristics of each of the growth patterns.…”
Section: Histologic Growth Patterns Of Liver Metastasesmentioning
confidence: 80%
“…Namely, in patients with multiple liver metastases, one growth pattern generally predominates (95,96,98). Furthermore, the growth patterns depend on the tissue of origin of the primary tumor (94,95,99).…”
Section: Histologic Growth Patterns Of Liver Metastasesmentioning
confidence: 99%
See 1 more Smart Citation